Peran Pemerintah Daerah Terhadap Pemberdayaan UMKM Tenun Ikat di Kota Kupang (Studi Pada Dinas Koperasi dan UMKM Kota Kupang) - Mone, Ikesy Maresa; Tameno, Nikson; Tiwu, Maria Indriyani H. (Innovative: Journal Of Social Science Research, 2024)
This research aims to determine how the Department of Cooperatives and MSMEs (Micro, Small, and Medium Enterprises) performs its role as a facilitator, regulator, and catalyst in empowering the ikat weaving MSMEs in Kupang City. This type of research uses descriptive research, which is included in qualitative research methods, a method that requires in-depth understanding. The data collection techniques used in this research are interviews, observations, and documentation. The results of this study show that the Department of Cooperatives and MSMEs in Kupang City, in its role as a facilitator, provides assistance in the form of weaving tools and raw materials, conducts training to improve skills, and helps with product promotion and marketing. As a regulator, the Department of Cooperatives and MSMEs in Kupang City has not issued specific regulations regarding tenun ikat MSMEs, but rather follows Government Regulation No. 7 of the Year. The role as a catalyst is seen from the implementation of the facilitator and regulator roles, which have had a positive impact on the development of tenun ikat MSMEs in Kupang City. The factors influencing the role of the Department of Cooperatives and MSMEs in empowering ikat weaving MSMEs in Kupang City are external and internal factors.